Modelo Dinámico de Emprendimiento y Asociatividad como Herramienta de Desarrollo Social para la Educación Media - Rodríguez Valbuena, Luisa Fernanda; González Rodríguez, Leonardo José (Ingeniería, 2004)
This article presents a model developed in systems dynamics, which it allows to describe the behavior in the time of the entrepreneurship and associability phenomena, like complementary mechanism to the intervention plan or qualification program in teachers and students at the involved schools. This intervention plan was based on the promotion of the associability and the competitions for the entrepreneurship, like tool for the improvement of the High School Education, and looked for as well to hit in communities of high socioeconomic vulnerability.